Anti‐N‐methyl‐d‐aspartate receptor encephalitis in Māori and Pacific Island children in New Zealand. (22nd March 2017) - Jones, Hannah F; Mohammad, Shekeeb S; Reed, Peter W; Dunn, Paul P J; Steele, Richard H; Dale, Russell C; Sharpe, Cynthia
Abstract : Aim: To investigate the incidence and severity of anti‐ N ‐methyl‐d ‐aspartate (anti‐NMDA) receptor encephalitis in children from New Zealand. Method: A retrospective case series was undertaken of all children (≤18y) diagnosed with anti‐NMDA receptor encephalitis from January 2008 to October 2015. Results: Sixteen patients were identified with anti‐NMDA receptor antibodies in the cerebrospinal fluid, three of whom had an associated teratoma. Fifteen children had Māori and/or Pacific Island ancestry. The incidence of anti‐NMDA receptor encephalitis in Māori children was 3.4 per million children per year (95% confidence interval [CI] 1.4–7.0) and the incidence in Pacific children was 10.0 per million children per year (95% CI 4.3–19.8) compared with 0.2 per million children per year (95% CI 0.0–1.0) in children without Māori or Pacific Island ancestry. Sixty‐seven per cent of children had a good outcome (modified Rankin Score ≤2) at 2 years' follow‐up. This compares unfavourably with other cohorts despite a shorter median time to first‐line immunotherapy (13d; range 4–89) and a higher proportion of children being treated with second‐line therapy (50%). Interpretation: Māori and Pacific Island children have a higher incidence of anti‐NMDA receptor encephalitis and possibly a more severe phenotype. These data suggest a genetic predisposition to anti‐NMDA receptor encephalitis in these populations. What this paper adds: Māori and Pacific Island children are at increased risk of anti‐ N ‐methyl‐d ‐aspartate (NMDA) receptor encephalitis (3.4 and 10.0 per million children per year respectively). One third of Māori and Pacific Island children with anti‐NMDA receptor encephalitis have a poor outcome. This article is commented on by Njafang and Missa on page673 of this issue. Video Podcast:https://youtu.be/0ZDY574Mr6Q